Nutritional value of some commercial marine fishes - Al-Hamadany, Qusay H.; farnar, Khalid W.; Jabir, Amir A.; Al-Anber, Luma J. (Iraqi Journal of Aquaculture, 2023)
The study included a comparability of the chemical composition and nutritional value of four economical fishes species from Iraqi coastal waters in northwestern the Arabian gulf: The species including Tenualosa ilisha, Acanthobagrus arabicus, Otoliths ruber, and Planiliza subviridis. Samples were brought from the local markets in Basra governance-southern of Iraq. Results show that the moisture of fish`s muscles was recorded from 69.15 ± 0.91% to 76.83 ± 0.15%, the protein was 16.93 ± 0.15 to 19.56 ± 0.83%, fat content was recorded from 1.64 ± 0.22 to 9.92 ± 0.51%, and ash from 1.81 ± 0.12 to 4.08 ± 0.08%. The statistical analysis shows that there were significant differences (p < 0.05) between the four species in some of the chemical composition ratios above. The nutritional value of energy was recorded from 112.435 to 194.835 Kcal/ 100 g. The findings of this study demonstrate that fish found in Iraqi marine waters serve as a primary source of protein and fat. This information can be useful to consumers, highlighting the nutritional benefits of consuming fish species rich in high-quality food content. Specifically, the Al-Nuweibi Otoliths ruber species should be periodically considered due to its high proportion of animal protein, which can aid in growth and muscle development.